Implementasi Manajemen Pengetahuan di Lingkungan Badan Pendidikan dan Pelatihan Keuangan - Akhmad Khabibi; Rokhmat Taufiq Hidayat (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Knowledge management has three important elements that can affect the successful implementation of knowledge management, namely people, process, and technology. The implementation of knowledge management within the Ministry of Finance officially began when the Minister of Finance Regulation Number 226 of 2019 concerning Knowledge Management in the Ministry of Finance was issued. However, the implementation of knowledge management has actually been going on for quite a long time at the Ministry of Finance, including the Financial Education and Training Agency as one of the echelon I units within the Ministry of Finance. This study tries to identify various forms of knowledge management implementation within the Financial Education and Training Agency considering that in the Minister of Finance Regulation Number 226 of 2019 the Financial Education and Training Agency has a more role in the management of knowledge management at the Ministry of Finance level. The results of the study indicate that the Financial Education and Training Agency has implemented knowledge management in various forms, especially related to elements of knowledge management, both related to people, process, and technology.